PERANCANGAN PENYULANG SPINDEL PADA MOTOR INDUKSI POMPA BANJIR - Irvan Buchari Tamam; Aas Wasri Hasanah; Raka Primipara (Sekolah Tinggi Teknik - PLN, 2016)
Increasing the amount of induction motor power available then the current on the induction motor will grow larger but to reduce the current is too large can be overcomeby increasing the voltage or increased voltage. In addition, one of the disadvantages of the induction motor is not able to maintain its speed with a constant when there is achange of load. If there is a change in load then the speed of the induction motor will decrease. Based on the results of the repeater design performed shows that a largeinduction motor that is Start UP BFP (Boiler Feed Pump) with 5191 KW at flood pumps Pluit Reservoir North Jakarta can be started directly if the flicker problem can be solvedimmediately and using spindle feeder network by considering relay aspect Used, both the inverse relay and the instant trip relay. The design results using almunium cablemeasuring 95 mm2 for 20KV voltage and 400mm2 almunium cable for 10KV voltage, 20 / 10KV transformer.